BRAND PERSONALITY CREATION THROUGH ADVERTISING (Study KFC on Television Commercial Break) - Mumu, Richard Laurenz; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
The perfect concept of Advertising and its application on the mass media cannot be separated with one central aspect from any sold product or certain service, named Brand personality and depends on five main aspects, which are Sincerity, Excitement, Competence, Ruggedness and Sophistication, especially for Kentucky Fried Chicken in Manado City.This research’s purposes  are to figure out whether Brand Personality give significant influence to the Advertising of KFC at Manado City, simultaneously and to figure out whether Brand Personality give significant influence to the Advertising of KFC at Manado City, partially. To achieve those objectives, Multiple Regression Analysis is used. Its’ conclusions are Brand Personality   generally give the significant influence for the Advertising of KFC and  each Brand Personality partially give the significant influence for the Advertising of KFC. Based on the results, company’s managers and employees must maintain and enhance the good understanding about three Brand Personality, must improve customers’ understanding about Sophistication and Excitement, and must give more concern about other influencing factors of the customers’ understanding about the advertising and its contents. Keywords : brand personality, advertising